Enhancing Productivity through the Transformation of Performance, Competence, and Commitment at PT. Indonesia Bulk Terminal - Dayuk Agustina; Vera Firdaus; Dewi Andriani (Perkumpulan Dosen Muda (PDM) Bengkulu, 2026)
Purpose: This study aims to analyze the effects of performance transformation, competence, and commitment on employee productivity at PT. Indonesia Bulk Terminal (IBT). Methodology: A descriptive quantitative research design was employed, utilizing purposive sampling technique with 100 permanent employees as respondents. Data were collected through a Likert-scale questionnaire and analyzed using SmartPLS 4.0 software, including Outer Model evaluation (convergent validity, discriminant validity, AVE, Composite Reliability), R², and path coefficient estimation with bootstrapping. Results: The results indicate that performance transformation positively and significantly affects productivity (T = 5.161, p = 0.000), competence positively and significantly affects productivity (T = 3.274, p = 0.001), while commitment has a significant but negative effect on productivity (T = 2.315, p = 0.021). The three independent variables collectively explain 67.1% (R² = 0.671). Findings: This study highlights that performance and competency transformation play an important role in improving productivity, while commitment does not have a significant direct effect on productivity. Novelty: Reveals unexpected negative influence of employee commitment on productivity in Indonesian bulk terminals. Originality: first study testing performance, competence, and commitment transformations as productivity predictors at PT. Indonesia Bulk Terminal. Conclusions: Productivity increases through effective performance transformation and competency development, while high commitment alone is not enough without discipline and Standard Operating Procedure compliance. Type of Paper: Empirical research paper